The issue of alternative evaluation in teaching Arabic between supporters and opponents - Al-awaydhi, Wafaa Hafez; Al-harisi, Jaliyah Hassan (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the percentage of both supporters and opponents of the alternative evaluation, detect the reasons for both support and opposition to the alternative evaluation from the viewpoint of teachers of the Arabic language in the Kingdom of Saudi Arabia. The survey descriptive method was used, the research sample consisted of (150) male and female teachers, and the researcher prepared a questionnaire to collect data. The results showed that (70.67%) of the total research sample are supporters for the alternative evaluation, whereas, (29.33%) of the total research sample are opponents to the alternative evaluation. The most important reasons of supporting the alternative evaluation were: the alternative evaluation is based on placing the student in real situations or simulating the reality and monitoring his responses in it, and achieving justice in the evaluation of students, and provides multiple opportunities for students to master the academic subject, and makes students use their skills and knowledge to accomplish any task, and allows continuity of learning. The most important reasons of Opposition to the alternative evaluation were: The alternative evaluation is not appropriate due to the density of students and the nature of the special courses in the Arabic language, and it is difficult to properly apply it according to its rules, and it strives for the student due to a large number of tests. In light of the study results, some recommendations were formulated.
Keywords: Alternataive Evaluation; Teaching Arabic; Saudi Arabia; Supporter; Opponent